2019
DOI: 10.3390/v11100923
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations Evading Avian Immunity around the Receptor Binding Site of the Clade 2.3.2.1c Hemagglutinin Gene Reduce Viral Thermostability and Mammalian Pathogenicity

Abstract: Since 2007, highly pathogenic clade 2.3.2 H5N1 avian influenza A (A(H5N1)) viruses have evolved to clade 2.3.2.1a, b, and c; currently only 2.3.2.1c A(H5N1) viruses circulate in wild birds and poultry. During antigenic evolution, clade 2.3.2.1a and c A(H5N1) viruses acquired both S144N and V223I mutations around the receptor binding site of hemagglutinin (HA), with S144N generating an N-glycosylation sequon. We introduced single or combined reverse mutations, N144S and/or I223V, into the HA gene of the clade 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Conversely, the unglycosylated epitopes of rSL20(P)-MVV310PB2 may be the major target of humoral immunity, but the antibody cannot bind to the epitopes of r310-NS28 due to the steric hindrance of the N-glycans. The result supports the importance of the epitopes and the preferred acquisition of 144N or 158N glycans to evade vaccine-induced antibodies by clade 2.3.2.1c H5N1 viruses [63]. A limitation of our study was that the inactivated virus antigens were not assayed by HAU before the vaccine was administered as a vaccine.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Conversely, the unglycosylated epitopes of rSL20(P)-MVV310PB2 may be the major target of humoral immunity, but the antibody cannot bind to the epitopes of r310-NS28 due to the steric hindrance of the N-glycans. The result supports the importance of the epitopes and the preferred acquisition of 144N or 158N glycans to evade vaccine-induced antibodies by clade 2.3.2.1c H5N1 viruses [63]. A limitation of our study was that the inactivated virus antigens were not assayed by HAU before the vaccine was administered as a vaccine.…”
Section: Discussionsupporting
confidence: 74%
“…SL20wt is classified into the genotype S H9N2 viruses in China along with N20-99 and SD1844 [33,37]. It shares the common MPMs found in most genotype S H9N2 viruses, including I292V and V598I in the PB2 gene, Q226L in the HA gene, a 3 amino acid deletion (63)(64)(65) in the stalk region of NA, N30D, and T215A in the M1 gene, and P42S and a C-terminal truncation from 237 to 217 amino acids in the NS1 gene, etc. (Table S2) [15,[24][25][26][38][39][40][41][42][43][44][45][46].…”
Section: 1mentioning
confidence: 99%
“…Highly pathogenic avian influenza viruses displayed a higher thermostability compared with viruses with low pathogenicity [ 68 ]. The resistance of HA to high temperatures contributes to environmental resistance in viruses [ 69 ] and affects pathogenicity in sensitive mammalian hosts [ 70 ]. Pathogenicity for animals of the SA may be associated with more pronounced thermostability of its HA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, phenotypic attributes conferred by one amino acid substitution may not be conferred if another amino acid was selected for at the subsite. Although an American-lineage R144G (H5: R140G; H7: R133G) escape mutant described above had increased affinity to numerous α-2,3 receptor analogues, subsequent phenotypic characterization of a gs/Gd-lineage escape mutant containing the N144S substitution (H5: N140S; H7: N133S) had reduced binding to 3′SLN-PAA receptor analogue and to chicken erythrocytes, and exhibited a reduction in thermostability compared the parental strain (An et al 2019 ). Another study characterizing Eurasian non-gs/Gd-lineage escape mutants containing S145P/Y substitutions (H5: 141; H7: 134) demonstrated that HA thermostability of escape mutants was dependent on this amino acid (Timofeeva et al 2020a ), and HI activity has been shown to be modulated by the amino acid present at subsite 57 (immature protein: 65) (Henry Dunand et al 2016 ).…”
Section: Molecular Determinants Of Haemagglutinin Antigenic Driftmentioning
confidence: 99%